Aflatoxin – Publication analysis of a global health threat. (July 2018) - Klingelhöfer, Doris; Zhu, Yun; Braun, Markus; Bendels, Michael H.K.; Brüggmann, Dörthe; Groneberg, David A.
Abstract: Background: As a metabolite of Aspergillus flavus and Aspergillus parasiticus, Aflatoxin is a carcinogenic and mutagenic mycotoxin that is confirmed as a class-1 agent. It contaminates the most of our staple foods, affecting 25% of global crops. It is a global threat to human health by causing liver cancer in conjunction with Hepatitis B. Developing countries are particularly at risk not only because of the climatic but also of the agricultural production conditions. Climatic change and the intensification of global trading are also enhancing the risk of the global contamination. The overall health effects are dramatic. Methods: Therefore, we choose this mycotoxin for an in-depth analysis of its global scientific publication output. The focus is on the geographical and chronological facts and trends, the international networks and the development of research fields. For this purpose, the bibliometric data was collected in the Web of Science database and interpreted according to a variety of scientometric parameters. Results: The results show a superiority of the USA regarding the absolute publication numbers that was taken over by China in 2016. Not only the dramatic incidence and prevalence rates of liver cancer and the high Aflatoxin contamination rate in China, but also the immense increase of the expenditure for research and development play a role. In relation to the integration of socio-economic features other countries emerge, i.e. Tunesia, Nigeria or Egypt. Other severely affected countries of Africa, Asia and South-America show a relatively low publication output. India, as an emerging country, achieves a considerably high output. Here, the health hazards are threatening and resulted in an outbreak of Aflatoxicosis induced Hepatitis in 1974. Although an outbreak of Aflatoxicosis in Kenya caused the deaths of 120 people, Kenyan research output is relatively low. The analyses of the distribution over time in 5-year intervals showed the relative decrease of the research area Oncology, whereas Food Science & Technology gained proportionally importance. Conclusions: For future Aflatoxin studies, it is extremely important to carry out projects with the participation of the most affected countries and to support and enhance the knowledge growth of the individual farmers to establish more adapted production practices. Highlights: The publication superiority of the USA was taken over by China in 2016. Affected developing countries show a relatively low publication output. Project are necessary with the participation of the most affected countries. Global trading and climatic change will influence Aflatoxin contamination.